Implementación de un sistema web que permita la administración de planes de clases diarios de los docentes de la escuela fiscal “Enrique Rodríguez Fabregat” del cantón Archidona - Arcos Guerrero, Angel Vladimir (2015)
The investigation had as main purpose to implement a web system that has the ability to manage the lesson plans for teachers of fiscal School "Enrique Rodriguez Fabregat," Canton Archidona. Therefore, in this school like any other you need to plan their teaching and learning activities to teach their classes. The methods used were: to gather scientific concepts include developing lesson plans, analytical understanding structuring the process of developing lesson plans for teachers, descriptive since the problem components analyzed, to teach statistical data obtained as a result of empirical research. Observation instruments for a better understanding of the processes of development of lesson plans, the survey for the analysis of the results, the interview to the principal were applied, judgment and knowledge of the researcher to implement the web system to be implemented. After analyzing the results it is concluded that the implementation of the control system if the lesson plans for follow-up and monitoring is justified also enables teachers to develop lessons calmly, open and flexible. It also has a user manual considering user manual imagery and simple language so that they can take advantage of the 100% easily and efficiently presents.